STRUKTUR MODAL, PROFITABILITAS DAN NILAI PERUSAHAAN : EFEK MODERASI GOOD CORPORATE GOVERNANCE SAAT MASA PANDEMI COVID-19 (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to analyze the effect of Capital Structure, Profitability and Firm Value, the moderating effect of Good Corporate Governance Capital during the Covid-19 pandemic on companies listed listed in the Index Business 27. This type of research is quantitative, while according to the relationship between variables, this research is included in correlational research. This study uses a purposive sampling technique using the 2017-2020 financial statements. The data used is secondary data which is processed using SPSS 22 software. The analytical methods used are Normality Test, Classical Assumption Test, and Hypothesis Testing. The results showed that: (1) Capital Structure (DER) had a significant effect on Firm Value (TOBIN'S Q) (2) Profitability (ROA) had no significant effect on Firm Value (TOBIN'S Q) (3) Good Corporate Governance (Komindep ) had a significant effect to Firm Value (TOBIN'S Q) (4) Interaction of Good Corporate Governance (Komindep) with Capital Structure (DER) has no significant effect on Firm Value (TOBIN'S Q) (5) Interaction of Good Corporate Governance (Komindep ) with Profitability (ROA) has no effect significant to Firm Value (TOBIN'S Q).Keyword : Capital Structure, Profitability, Firm Value, Good Corporate Governance.